AB0501 Efficacy and safety of certolizumab pegol (CZP) with concomitant methotrexate (MTX) in korean rheumatoid arthritis (RA) patients (PTS) with an inadequate response to MTX. (23rd January 2014) - Kang, Y.M.; Park, W.; Park, Y.E.; Choe, J.Y.; Bae, S.-C.; Cho, C.S.; Shim, S.C.; Lee, S.K.; Suh, C.-H.; Cha, H.-S.; Song, Y.W.; You, B.; et al.
Abstract : Background: CZP as a concomitant therapy to MTX has shown rapid and sustained efficacy in RA pts in previous international clinical trials. Objectives: To confirm the efficacy and safety of CZP+MTX in Korean pts with active RA and an inadequate response to MTX. Methods: In this 24-week (Wk), double-blind, randomised, placebo (PBO)-controlled study, pts with active RA (≥9 tender/swollen joints, CRP >15 mg/L or ESR ≥30 mm/h) were randomised 2:1 to receive CZP (initial dose of 400mg at Wks 0, 2 and 4 followed by 200mg every 2 Wks) or PBO. Pts remained on stable dose MTX. Pts with no ACR20 response at both Wks 12 and 14 were withdrawn. Primary efficacy endpoint was ACR20 response at Wk 24. Secondary outcomes included ACR20 at Wk 12, ACR50/70 at Wks 12 and 24, change from baseline (CFB) in HAQ-DI at Wk 24 and safety. LOCF was used to impute missing values for the efficacy endpoints. Results: 121 pts (CZP N=81; PBO N=40) were included in efficacy analyses (mean disease duration=6.2yrs, mean DAS28[ESR]=7.4). Baseline characteristics were comparable between the 2 groups. The min-max MTX dose was 10-20 mg/Wk. ACR20 was significantly higher in the CZP vs PBO group at Wk 1 (P=0.013). This was maintained to Wk 24 (66.7% vs 27.5% P<0.001; figure). ACR50/70 responses were significantly higher in the CZP vs PBO groups at Wk 24 (figure). HAQ-DI, pain and global disease activity significantly improved in the CZP vs PBO groups at Wk 24. Mean CFB was -0.56 vs -0.14 for HAQ-DI (P<0.001), -28.9 vs -9.6 for pain (P<0.001), and -25.3 vs -13.5 for global disease activity (P=0.009). AEs were reported in 65.9% of CZP and 57.1% of PBO pts; none had a fatal outcome. The most common AEs in CZP pts were upper respiratory tract infections (25.9%) and abdominal pain (5.9%). SAEs were reported in 9.4% of CZP pts, including infections in 6pts, of which 2 had TB (background rate=88/100, 000 persons). 1 No SAEs were reported in the PBO group. Conclusions: CZP 200mg+MTX resulted in a rapid and sustained reduction in RA signs and symptoms, and improved physical function and pain compared with PBO+MTX. CZP had an acceptable safety profile. This confirms the efficacy and safety of CZP in MTX refractory RA. References: Dye et al. PLoS One. 2011; 6(6): e21161. Disclosure of Interest: None Declared